2021
DOI: 10.20885/jeki.vol7.iss2.art5
|View full text |Cite
|
Sign up to set email alerts
|

Do stability and size affect the profitability of Islamic rural bank in Indonesia?

Abstract: Purpose -This study aims to analyze the effect of stability, size, financial performance and macroeconomic variables on the profitability of Islamic Rural Banks (BPRS) in Indonesia.Methodology -This study uses panel data consisting of 82 BPRS from December 2012 to December 2018. This study uses a dynamic model using GMM (General Method of Moments) developed by Arellano & Bover (1995) and Blundell & Bond (1998). GMM is used to describe the actual conditions in the analysis of profitability of Islamic Rural Bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
(94 reference statements)
0
9
0
1
Order By: Relevance
“…The higher the financing provided by the bank has the opportunity to increase profits because the main income for IRBs comes from financing. Al-Harbi (2019) and Sudarsono et al, (2021) in their research found a positive and significant effect between FDR and profitability. While Purwasih & Wibowo (2021) actually found a negative effect, while Irwan (2017) found that there was no effect between FDR and profitability.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The higher the financing provided by the bank has the opportunity to increase profits because the main income for IRBs comes from financing. Al-Harbi (2019) and Sudarsono et al, (2021) in their research found a positive and significant effect between FDR and profitability. While Purwasih & Wibowo (2021) actually found a negative effect, while Irwan (2017) found that there was no effect between FDR and profitability.…”
Section: Introductionmentioning
confidence: 91%
“…The novelty of this study is to examine the financing scheme that contributes to profitability between profit margin financing (PMF) and profit-sharing financing (PSF), which has not been widely studied. Only Kuswara, Puji Lestari, & Retnaningsih (2019) examined the effect of mudharabah financing, musyarakah financing and mudharabah financing on ROA, while most researchers used financial ratio variables such as FDR, NPF, CAR, OEIR as variables affecting profitability (Sudarsono et al, 2021;Jaouad & Lahsen, 2018;Widarjono &Anto, 2020 andSaid &Ali, 2016). The results of this study are very meaningful for the management of Islamic banks in making decisions on financing schemes which so far have been dominated by low-risk PMFs compared to high-risk PSFs.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…ROA merupakan rasio yang mengindikasikan kesuksesan bank syariah dalam menghimpun laba (Mujaddid & Wulandari, 2017). ROA merupakan indikator kinerja bank untuk menghasilkan laba sebelum pajak dari total rata-rata aset yang dimiliki (Sudarsono, et al, 2021;Pertiwi et al, 2020). Adapun semakin besar ROA maka akan berbanding lurus dengan keuntungan yang didapatkan (Santoso dan Sukihanjani (2013).…”
Section: Pendahuluanunclassified
“…Liquidity risk, as measured by the financing to deposit ratio (FDR), shows the amount of financing provided compared to public deposits, so the larger the FDR, the greater the financing provided [5]. IRBs are very interested in FDR because they can contribute profits to banks [6,7]. The higher the FDR, the higher the financing.…”
Section: Introductionmentioning
confidence: 99%